2013
DOI: 10.1097/sle.0b013e318275b35f
|View full text |Cite
|
Sign up to set email alerts
|

Covered Self-Expandable Metallic Stents Could be Used Successfully in the Palliation of Malignant Cervical Esophageal Strictures

Abstract: According to our limited number of cases, placement of covered self-expandable metallic stents into the cervical esophagus can be performed safely, and significant improvement of dysphagia scores and life quality of patients can be obtained instantly after the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Oral meal intake becomes difficult, therefore, patients typically present with a nutritional disorder. Furthermore, dysphagia often leads to the aggravation of Karnofsky performance status (1) and a decrease in patient quality of life (26). The optimal palliative treatment for this type of dysphagia has yet to be established, however, stent placement (2), intracavitary radiotherapy (ICRT) (3) or external beam radiation therapy (EBRT) (4) are currently employed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral meal intake becomes difficult, therefore, patients typically present with a nutritional disorder. Furthermore, dysphagia often leads to the aggravation of Karnofsky performance status (1) and a decrease in patient quality of life (26). The optimal palliative treatment for this type of dysphagia has yet to be established, however, stent placement (2), intracavitary radiotherapy (ICRT) (3) or external beam radiation therapy (EBRT) (4) are currently employed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dysphagia often leads to the aggravation of Karnofsky performance status (1) and a decrease in patient quality of life (26). The optimal palliative treatment for this type of dysphagia has yet to be established, however, stent placement (2), intracavitary radiotherapy (ICRT) (3) or external beam radiation therapy (EBRT) (4) are currently employed. In cases where it is not possible to use these treatment strategies or when their effects are insufficient, enteral nourishment via a gastrostomy tube or central vein nourishment is performed (7).…”
Section: Introductionmentioning
confidence: 99%
“…T he use of self-expanding metallic stents at the level of the cervical esophagus and/or hypopharynx is restricted and considered unfeasible because of the risks of stent displacement, tracheal compression, bleeding, severe pain, foreign-body sensation, and limitations of the cricopharyngeal sphincter. Studies have reported the safety and effectiveness of metal biliary stents and stents with a smaller diameter when implanted at the level of the cervical esophagus and/or hypopharynx [1][2][3][4][5] for the treatment of cervical esophageal or hypopharyngeal stenosis.…”
mentioning
confidence: 99%
“…Essa tecnologia também é aplicada para paliação de lesões no esôfago cervical, onde o implante da prótese pode ser desafiador. Estudos demonstram que PMAEs com desenho específico podem ser implantadas de forma segura e eficaz no segmento cervical do esôfago (Bayratkar et al 2013;Battaglia et al 2016 Não existe consenso na literatura quanto à definição do tempo que se considera para um evento adverso relacionado à prótese metálica de esôfago ser intitulado de evento adverso de longo prazo, variando de 4 semanas após a inserção da prótese inicial (Homann et al, 2008) até 120 dias (Schoppmann et al, 2013).…”
Section: Malufunclassified